English English: Bahasa Indonesia - Kristiantono, Bazar; Sumardiono, Sumardiono (ENGLISH RESEARCH JOURNAL, 2024)
This research describes how Joker movie's portrayal of main character’s mental health was affected by child abuse. Descriptive qualitative method was employed in this study. It concentrated on the effects of child abuse. The Joker movie and its script were used as the research data. The researcher obtained well-structured, conveniently analyzed research data by note-taking, documentation the investigation, and acquired still photos from movies. The psychoanalysis theory of Sigmund Freud (1960) provides the framework for the data analysis method employed in this study. The findings of the research showed that the effects of child abuse that main character got as a child were mental disorders, namely Pseudobulbar Affect and Schizophrenia. Arthur Fleck's id and ego were the basis for the effects of child abuse seen in this film. Arthur's id was evident when he believed that his life is unfairness. Arthur's ego was evident when he killed those who had wronged him. The manifestation of Arthur's superego was evident in his refusal to kill those who had no issues with him and in his parental upbringing. Keywords: Child Abuse, Mental Health, Movie, Sigmund Freud, Psychoanalysis.